Drought-Induced Amplification of Saint Louis encephalitis virus, Florida - Jeffrey Shaman; Jonathan F. Day; Marc Stieglitz (Emerging Infectious Diseases, 2002)
We used a dynamic hydrology model to simulate water table depth (WTD) and quantify the relationship between Saint Louis encephalitis virus (SLEV) transmission and hydrologic conditions in Indian River County, Florida, from 1986 through 1991, a period with an SLEV epidemic. Virus transmission followed periods of modeled drought (specifically low WTDs 12 to 17 weeks before virus transmission, followed by a rising of the water table 1 to 2 weeks before virus transmission). Further evidence from collections of Culex nigripalpus (the major mosquito vector of SLEV in Florida) suggests that during extended spring droughts vector mosquitoes and nestling, juvenile, and adult wild birds congregate in selected refuges, facilitating epizootic amplification of SLEV. When the drought ends and habitat availability increases, the SLEV-infected Cx. nigripalpus and wild birds disperse, initiating an SLEV transmission cycle. These findings demonstrate a mechanism by which drought facilitates the amplification of SLEV and its subsequent transmission to humans.